Development and Characterization of Lithium Manganese Oxide Thinfilms for Li ion Micro Battery Application - Sankara Subaramanian*, N.; Balakrishnan, T. (Asian Journal of Chemistry, 2013)
LiMn2O4 thin films have been prepared by cost-effective spin coating method using the optimized coating conditions. The X-ray diffraction pattern of LiMn2O4 thin films confirms cubic spinel structure with the preferred orientation along the (111) plane. The other orientations observed correspond to (311), (400) and (440) plane. The sharpness and peak intensity of all the above prominent orientations increase with the increase in the number of coatings and spin rate. This may be attributed to the increase in degree of crystallinity, oriented growth of all the planes and densification of crystallite aggregates with the increase in number of coatings and spin rate. The lattice constant ‘a’ evaluated from the XRD data lies between 8.11619 and 8.13482 Aº. The mean grain size increases with the increase in the number of coatings and this may be attributed to the increase in the accumulation and adhesion of the crystallites on the substrate surface with the increase in the number of coatings. The micro strain and dislocation density of the LiMn2O4 thin films increases with the increase in the number of coatings and this may be ascribed to the increase in the close packing of crystallite aggregates, which ultimately increases the thermal and mechanical shock resistance to the substrate surface. The FTIR spectra of LiMn2O4 thin films deposited with different spin rate and number of coatings illustrates the high-frequency bands located around 623 cm-1 and 514 cm-1 and these are associated with the asymmetric stretching modes of the MnO6 group. A weak band observed at 437 cm-1 is attributed to the LiO4 tetrahedra. The AFM micrographs of the LiMn2O4 thinfilms deposited at 3000 rpm shows the uniform distribution of fine grains throughout the surface associated with the accumulation of fine grains without any dark pits, pin holes and cracks.